Territory quality and male dominance in Tropidurus torquatus (Squamata, Tropiduridae) - Kohlsdorf, Tiana; Ribeiro, Joana M.; Navas, Carlos A. (Phyllomedusa: Journal of Herpetology, 2006)
In territorial species, females are often attracted by high-quality territories, which are expected to be owned by males that successfully won competition with other males. Because morphological and behavioral traits frequently influence males' combat success, these parameters may be used by females to assess the male (and associated territory) quality. In the present study, we tested the hypothesis that organismal traits in dominant males of the lizard Tropidurus torquatus are associated with the quality of the territory owned. After characterizing the territories occupied, we used a discriminant analysis to test if morphological and behavioral traits of the dominant male predict the quality of the territory owned. High-quality territories were characterized by a larger number of refuges, shorter distances among shelters and a well-defined harem, in comparison with low-quality territories. Organismal traits predicted with 100% accuracy the type of the territory owned: high-quality territories were associated with larger males that had longer heads, while males occupying low-quality territories exhibited more head displays, traveled larger distances and ran slightly slower than those associated with high-quality territories. We discuss possible implications of territory quality and male traits for reproductive success in Tropidurus torquatus.